Pengaruh Locus of Control, Self Efficacy dan Employee Engagement Terhadap Kinerja Karyawan pada Objek Wisata Owabong Water Park Purbalingga - Maolana, Adnan; Pradhipta Aryoko, Yudhistira; Darmawan, Ahmad; Widyaningtyas, Dian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this study is to examine the influence of locus of control, self efficacy and employee engagement on employee performance at the tourist attraction of Owabong Water Park Purbalingga. The study is a quantitative study using a total of 112 respondents of permanent employees at owabong water park purbalingga. The simple sampling technique used is the method of saturated samples. The analysis technique used in this study is using the SPSS Version 26 tool. The tests used in this study include the Validity Test, Reliability Test, Normality Test, Multicolinearity test, Heteroscadastisity Tests, Dual Linear Regression Analysis Tests and F and T Tests. The results of this study show that locus of control has a positive and significant impact on employee performance, self efficacy has a significant and positive impact on the employee's performance, employee engagement has a partial and significant effect on employees' performance, and locus Of Control, Self Efficiency and Employee Engagement simultaneously have a positive effect on Employees' performance. The practical implications of this study are the need for companies to focus on developing strategies and programmes that can increase employee engagement levels, thereby improving employee overall performance.